Evaluasi Penerapan Kebijakan Pajak Natura Berdasarkan PMK Nomor 66 Tahun 2023 - Lady Chintya Purba; Arifin Rosid (Politeknik Ganesha Medan, 2025)
The Indonesian Government issued Minister of Finance Regulation Number 66 of 2023 as an implementing regulation of Government Regulation Number 55 of 2022. This new regulation aims to regulate the Income Tax treatment of income or compensation concerning work or services received in-kind. A study was conducted to evaluate the performance of PT. GXX in implementing the in-kind tax policy contained in PMK Number 66 of 2023. The research focused on examining the Company's tax system based on the principles contained in the Tax Control Framework. PT GXX operates in the logistics and offshore services sector, providing in-kind facilities to employees such as transportation, credit, accommodation in offshore locations, etc. The study was a single case study using a descriptive qualitative approach based on case studies. The evaluation results demonstrate that PT GXX can develop effective tax strategies by deeply understanding regulations and identifying areas impacted by the implementation of in-kind taxes. With substantial support from its tax consultants, the company can establish necessary control processes and document the entire tax implementation process. Proper division of duties and responsibilities and regular monitoring and internal audits can lead to a successful implementation of new tax regulations following the principles of TCF. Despite facing challenges such as a lack of government-provided socialization and training, PT GXX has shown its commitment to adopting TCF principles in implementing new tax regulations. Thus, this research provides recommendations for providing training to deepen tax knowledge further, create clear standard operating procedures, and maintain a proactive attitude and good communication between internal teams.